On detecting the dependence of time series - Dokuchaev, Nikolai (Taylor & Francis Inc, 2012)
The author suggests a heuristic method for detecting the dependence of random time series that can be used in the case when this dependence is relatively weak, such that the traditional methods are not effective. The method requires comparison of some special functionals on the sample characteristic functions with the same functionals computed for the benchmark time series with a known degree of correlation. Some experiments for financial time series are presented.